REVISITING SHAKESPEARE’S SONNETS: A QUEER-FORMAL READING OF GENDER IDENTITY - Hidayati, Hidayati; Zuindra, Zuindra; Geubrina, Misla; Wardana, Muhammad Kiki; Hia, Yuniarti (Universitas Islam Sumatera Utara (UISU), 2025)
This study aims to review the construction of gender identity in Shakespeare's sonnets in the context of contemporary gender theory and queer reading. A descriptive qualitative method is applied with a Formalism approach combined with queer theory (Butler, 1990; Sedgwick, 1990) and Marxist feminism (Federici, 2012). The primary data consists of five selected sonnets, Sonnet 20, 57, 62, 18, and 55, which are analyzed using close reading techniques, textual interpretation, and contextual analysis. The research steps include: (1) selecting sonnet texts based on the relevance of gender themes, (2) identifying formal elements (diction, structure, symbols), (3) analyzing meaning and power relations in the discourse of love and identity, and (4) drawing conclusions based on the theory used. The results of the study show five main findings. First, Sonnet 20 displays an ambiguous representation of gender, showing the shifting roles between masculine and feminine. Second, Sonnet 18 and Sonnet 87 depict homoerotic desire and power relations that transcend heteronormative norms. Third, Sonnet 57 shows the emotional ambiguity and identity of the poet as a passive subject and admirer. Fourth, Sonnet 62 reveals Time, Mortality, and the Search for Eternal Identity, while fifth, Sonnet 55 shows language, symbols, and performativity as spaces for identity formation. This study concludes that Shakespeare views identity as a fluid social and linguistic construction, and makes poetry a space for negotiation between love, time, and human existence.